1986
DOI: 10.1111/j.1432-1033.1986.tb09379.x
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization and amino acid sequence of m-type thioredoxins from spinach chloroplasts

Abstract: The complete primary structure of m-type thioredoxin from spinach chloroplasts has been sequenced by conventional sequencing including fragmentation, Edman degradation and carboxypeptidase digestion. As already reported [Tsugita, A., Maeda, K. & Schurmann, P. (1983) Biochem. Biophys. Res. Commun. 11.5, 1-71 these thioredoxins contain the same active-site sequence as thioredoxins from other sources. Based on the amino acid sequence thioredoxin mc contains 103 residues, has a relative molecular mass of 11 425 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…6). It is suggested that the evolution of the ancestral HSP70 began with an ancient 130-to 160-amino-acid domain corresponding to its N-terminal quadrant and probably related to the m-type thioredoxin (31) (Fig. 6, the ancestral HSP70 version, represented by those present in archaebacteria and gram-positive bacteria (stage III).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). It is suggested that the evolution of the ancestral HSP70 began with an ancient 130-to 160-amino-acid domain corresponding to its N-terminal quadrant and probably related to the m-type thioredoxin (31) (Fig. 6, the ancestral HSP70 version, represented by those present in archaebacteria and gram-positive bacteria (stage III).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence similarity between MreB and other HSP70s was comparable to the above percentage (Table 2). However, when alignment was carried out with other HSP70 sequences which do not contain the deletion in the N-terminal quadrant, then a large gap in the MreB sequence in the In addition to MreB, a somewhat lower but significant homology of HSP70 with the m-type thioredoxin from spinach chloroplast was also noted (31). Interestingly, this latter protein, which has only 104 amino acid residues, showed maximum similarity to the first quadrant of the HSP70 sequence from gram-positive bacteria.…”
Section: -D-kt-kv-e-a--a------le -I---q1---r---t--tn-lfa---li-rtasdpvmentioning
confidence: 99%
“…The chloroplastic sequences of thioredoxin/and m from higher plants are preceded by a transit peptide without any clear homologies even when they belong to very similar proteins. The N-terminal sequence of the mature proteins is not always easy to determine because of blocked N-termini except in the case of thioredoxin m (Maeda et al, 1986;Decottignies et al, 1990). The first third of the protein (amino-terminal part to the active site) is generally the least conserved part, the C-terminal part being much more similar in all the groups considered.…”
Section: Sequences and Evolutionmentioning
confidence: 99%
“…Plant and E. coli thioredoxin sequence names correspond to SWISS-PROT identification names. THII_TOBAC: tobacco thioredoxin h 2 (Brugidou et al, 1993); THIH_TOBAC: tobacco thioredoxin h 1 (Brugidou et al, 1993); THIF_SPIOL: spinach thioredoxin f (Kamo et al, 1989); THIM_SPIOL: spinach thioredoxin m (Maeda et al, 1986); THIO_ECOLI: E. coli thioredoxin (Hö ö g et al, 1985). (c) Sequence alignment of CDSP 32 N-terminal 121 residues and C-terminal 122 residues.…”
Section: Cloning Of a Cdsp 32 Transcript And Sequence Analysis Of Thementioning
confidence: 99%